Rotate to Elevate: Examining Job Rotation and Teamwork Effects on Employee Performance in Port Management Industry - Munawaroh, Munawaroh; Sugiawan, Rizki; Ilham, Ilham; Rachmat, Luthfi; Murtado, Ahmad (Cv. Syntax Corporation Indonesia, 2026)
Port management organizations face performance optimization challenges that require strategic human resource interventions. This quantitative research examines the influences of job rotation and teamwork on employee performance within the Indonesian port industry context. Employing census sampling of 123 employees at PT PCM—a regional government-owned port enterprise in Cilegon—data were collected through validated questionnaires and analyzed using multiple linear regression. Findings reveal that job rotation demonstrates significant positive effects on performance (, ), indicating that systematic position changes enhance employee competencies and adaptability. Teamwork exhibits a positive but non-significant relationship with performance (, ), suggesting that collaborative processes require additional mediating factors to translate into performance gains. The combined variables explain 62.6% of performance variance (), confirming the substantial contribution of human resource development strategies. This research contributes empirical evidence supporting job rotation as an effective performance enhancement mechanism in port management contexts, while revealing the complexity of teamwork that requires deeper investigation. Practical implications emphasize the implementation of strategic rotation programs and the examination of team effectiveness factors for optimizing port industry workforce performance. Study limitations include the single-organization focus and cross-sectional design, suggesting the need for longitudinal and multi-site investigations to enable broader generalization.